2015
DOI: 10.1161/cir.0000000000000329
|View full text |Cite|
|
Sign up to set email alerts
|

Pediatric Pulmonary Hypertension

Abstract: Abstract-Pulmonary hypertension is associated with diverse cardiac, pulmonary, and systemic diseases in neonates, infants, and older children and contributes to significant morbidity and mortality. However, current approaches to caring for pediatric patients with pulmonary hypertension have been limited by the lack of consensus guidelines from experts in the field. In a joint effort from the American Heart Association and American Thoracic Society, a panel of experienced clinicians and clinician-scientists was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
453
0
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 949 publications
(468 citation statements)
references
References 656 publications
(689 reference statements)
7
453
0
8
Order By: Relevance
“…This notion is supported by longitudinal studies that identified PA stiffness as a highly significant (P , 0.001) predictor of mortality in a cohort of 86 patients with pulmonary arterial hypertension (PAH) during a follow-up of 48 months (5). In addition to its…”
Section: Vascular Calcification In Pulmonary Hypertensionmentioning
confidence: 86%
See 1 more Smart Citation
“…This notion is supported by longitudinal studies that identified PA stiffness as a highly significant (P , 0.001) predictor of mortality in a cohort of 86 patients with pulmonary arterial hypertension (PAH) during a follow-up of 48 months (5). In addition to its…”
Section: Vascular Calcification In Pulmonary Hypertensionmentioning
confidence: 86%
“…Although this may likely represent a confounding effect or a common causality of these clinical parameters on the relationship of HDGF and outcome as the authors suggest, this also limits the additive clinical benefit of HDGF measurement in predicting outcome, as these measures are already obtained as part of routine clinical practice. In PAH, there is an important need for biomarkers or other noninvasive measures that reliably predict invasive hemodynamics to limit the need for serial cardiac catheterizations, with the attendant risk for morbidity and mortality (5). From the authors' analysis, HDGF does not appear to meet this need.…”
Section: The Prescient Prognosticator? Hepatoma-derived Growth Factormentioning
confidence: 98%
“…Por otro lado, la cateterización cardíaca permite también la detección de lesiones como estenosis de vena pulmonar y colaterales que pueden presentarse en DBP, pero que no son fáciles de diagnosticar mediante ecografía. Es por esto que las guías de Hipertensión Pulmonar publicadas por la American Heart Association recomienda considerar el cateterismo cardiaco en algunos casos específicos como: 1) signos persistentes de enfermedad cardiorrespiratoria severa o deterioro clínico no explicado directamente por otra evaluación diagnóstica; 2) sospecha de tener HP significativa a pesar de manejo óptimo; 3) consideración de terapia vasodilatadora crónica; 4) presentación de edema pulmonar recurrente inexplicado 7,12 .…”
Section: Evaluaciónunclassified
“…Prostanoides de uso sistémico como epoporostenol han sido usado en algunas series, pero causan hipotensión sistémica lo que limita su uso. Con la evidencia disponible en niños, las guías clínicas de la AHA para la HP del 2015 concluyen que los usos de estas terapias específicas pueden ser útiles cuando se han manejado todas las causas subyacentes tanto pulmonares como cardía-cas 12 . En nuestro centro empleamos habitualmente inicio de tratamiento con sildenafil como primera lí-nea cuando los pacientes presentan HP secundaria a DBP severa, luego de haber evaluado y tratado pertinentemente otras posibles etiologías subyacentes.…”
Section: Terapias Específicasunclassified
“…Hemodynamic assessment with HC is the standard tool used to evaluate hemodynamics at presentation and in reassessment after targeted therapy 3. The overall adverse event (AE) rate with pediatric HC is relatively low at 0.1%4; however, HC in children with PH is substantially higher, with cardiac arrest occurring in 4% to 6% 5, 6…”
mentioning
confidence: 99%